In vivo use of Campath-1G to prevent graft-versus-host disease and graft rejection after bone marrow transplantation. - Willemze, R; Richel, D; Falkenburg, J; Hale, G; Waldmann, H; Zwaan, F; Fibbe, W (1992)
Twenty-two patients (16 male, six female; median age 34 years, range 16-49) with acute myeloid leukemia (1st complete remission (CR), n = 9), acute lymphocytic leukemia (1st CR, n = 5), chronic myeloid leukemia (chronic phase n = 5, accelerated phase n = 1), malignant lymphoma (n = 1) and myeloma (n = 1) were transplanted with unmanipulated donor bone marrow after standard conditioning including the monoclonal antibody Campath-1G daily from day -4 to day 0. No further graft-versus-host disease (GVHD) prophylaxis was given. All patients engrafted and neither graft failure nor rejection were observed. Acute GVHD grade I (skin) was seen in 12 out of 21 patients at risk. Acute GVHD grade II (skin) occurred in two patients. Severe GVHD (grade III, IV) of the gut, liver and skin developed in two patients. The overall incidence of severe acute GVHD (II-IV) was 19% of the patients at risk. Chronic GVHD (skin only) was seen in eight patients (42%) (six of extensive severity). A total of 14 patients died, the causes being relapse (four), direct cytotoxic drug toxicity (one), a GVHD (two), disseminated varicella zoster (one), systemic tuberculosis (one), interstitial pneumonitis (three) and veno-occlusive disease (two). These results indicate that the intravenous administration of Campath-1G may have reduced the incidence of severe acute GVHD without the occurrence of graft failure. However, the incidence of chronic GVHD does not appear to have decreased.